Pemodelan Design Thinking dalam Perancangan UI dan UX Aplikasi Jasa Potong Rumput CleaningKuu - Finanta Okmayura; Melly Novalia; Vitriani Vitriani (Jurnal SAINTIKOM (Jurnal Sains Manajemen Informatika dan Komputer), 2023)
A grass cutter is a tool used to cut grass or plants. At present, data and information related to lawn mower rental services are still conventional, namely obtained through word of mouth and print media such as newspapers, pamphlets, and magazines. Because the media used is limited, consumers have problems finding information about the grass cutting service assistance business. The problems experienced by consumers are the lack of various information, such as the address of the rental place, the unavailability of the process for renting the lawn mower service online, and the absence of official prices for lawn mowing services listed in newspapers and flyers so that the price can be manipulated according to the wishes of the service provider. To solve these problems, a car-based lawn mower application was designed that can make it easier for users and more efficient by using design thinking and modeling. The stages of the Design Thinking process start with the empathize, define, ideate, prototype, and test stages. After designing the user interface, testing was then carried out using the System Usability Scale (SUS) approach, and a score of 81 was obtained, which was in grade B, so it can be concluded that the design of the user interface application for mowing services is feasible to be developed into a mobile-based application.